Dynamic simulation of coastal wetlands for Guangdong-Hong Kong-Macao Greater Bay area based on multi-temporal Landsat images and FLUS model - Hongjiang Guo (Elsevier, 2021)
Coastal wetlands play a vital role in coastline protection. Coastal landscape of the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) has changed drastically. In order to explore the process and law of coastal landscape dynamics in GBA, in this research, multi-temporal Landsat images and proposed hybrid object-based image analysis and multi-level decision tree classification were applied to monitor the changing trends and current status of the coastal landscape in GBA from 1988 to 2018. There were 5818.58 km2 of natural wetlands in 2018, including mangroves (39.62 km2), tidal flats (73.64 km2), rivers (161.65 km2), and shallow seas (5543.67 km2). Due to the influence of anthropogenic activities, natural wetlands showed a decreasing trend, while artificial wetlands and non-wetlands have been increasing. Results indicated that the landscape in the study area showed a trend of fragmentation, the degree of landscape aggregation weakened, the dominant patches were scattered, the shape became more and more complex, and the landscape heterogeneity increased. Then, a future land use simulation model was used to simulate the coastal landscape change trends of GBA in 2028 under four scenarios. The mangrove has the fastest growth rate of 1.47 km2/a under wetland protection scenario. The tidal flat and paddy field would increase under scenarios of the wetland protection and farmland protection, respectively. The construction land has the fastest growth rate under the economic development scenario and would be 47.56 km2/a. Woodland, dry land, and culture ponds are further transformed into other landscape types, while rivers, shallow seas, and reservoirs/ponds have no obvious change.